Comparison of brachial artery endothelial function in the dominant arm between male college baseball pitchers and fielders - Morimoto, E.; Matsui, M.; Mori, S.; Kumakura, T.; Konishi, M.; Michinobu, R.; Fukuda, T.; Takemura, M.; Kosaki, K. (The Journal of Strength and Conditioning Research, 2025)
Although structural changes caused by exercise-induced vascular adaptation have been reported in baseball players, current evidence in the literature concerning vascular function remains limited. This cross-sectional study aimed to determine whether vascular endothelial function in the brachial artery of the dominant arm differed between university baseball pitchers vs. fielders. Ninety baseball players participated in this study. Brachial artery diameter and vasodilator function were measured in the supine position for each subject using an ultrasound imaging system. Shoulder joint range of motion and muscle strength were measured in supine and prone positions. Compared with the fielders, the pitchers had a decreased mean flow-mediated dilation (FMD) values (7.5% ± 2.5 vs. 10.6% ± 4.0%, p < 0.001) but significantly higher values for range of motion regarding external rotation (ER) of the shoulder joint (119.8 ± 8.5° vs. 115.7 ± 7.8°, p = 0.035), ER muscle strength (7.6 ± 2.2 N vs. 6.2 ± 2.0 N, p = 0.009), and baseline brachial artery diameter (4.2 ± 0.4 mm vs. 4.0 ± 0.4 mm, p = 0.010). Simple correlation analysis showed a negative correlation among FMD values, shoulder joint internal rotation strength, and ER range of motion. These findings indicate that functional exercise-induced vascular adaptations occur in the brachial artery of pitchers, indicating a possible role for position-specific demands in vascular remodeling.